The relation of the state to the railways - Murphy, Joseph John (Statistical and Social Inquiry Society of Ireland, 1867)
A notion, however, appears still to exist, that State intervention for the purpose of making railways more useful would be "a relaxation of the strict principles of political economy, to be justified, if at all, only by the exceptional circumstances of Ireland." Now this is a double misconception. Ireland is, no doubt, a poorer qountry than Great Britain; but to relax the application of the principles of political economy in the case of a poor country, would be as reasonable as to relax the application of medical science in the case of a patient of weak constitution. And the intervention of the State for the purpose of providing the country with the most efficient railway communication possible is not opposed to the principles of political economy. In every country in the world stone roads are a matter of State concern, and are paid for out of the taxes. Every one regards this as a duty of the State, and it is impossible to give any good reason, other than one of mere convenience, why the same rule should not be applied to iron roads.
Read Tuesday, 24th April, 1866
Keywords: Irish railways; State owned railways; 314.15